ESG Disclosure and Firm Performance: Evidence on Profitability, Market Value, and Cost of Debt from Indonesia - Audrey Michelle Wenny Yolanda; Darmawati Darmawati; Baginda Hamzah; Andi Raina Ananda Herdiyana (Global Research Collaboration, 2026)
The growing prominence of Environmental, Social, and Governance (ESG) initiatives has prompted extensive debate regarding their financial consequences, particularly within emerging economies where empirical findings remain limited. This study explores the influence of ESG disclosure on firm performance among Indonesian companies listed in the Kompas100 index from 2017 to 2023. Employing unbalanced panel data regression models, the analysis evaluates three financial dimensions: profitability, market valuation, and cost of debt. The results indicate that ESG disclosure has a positive and statistically significant impact on profitability, suggesting that greater transparency in sustainability practices enhances operational efficiency and strengthens internal financial outcomes. Conversely, the association between ESG disclosure and market valuation is positive yet statistically insignificant, implying that investors in Indonesia’s capital market have not fully incorporated ESG considerations into their valuation processes. Moreover, ESG disclosure exhibits a negative but insignificant relationship with the cost of debt, indicating that lenders have not systematically embedded ESG factors into credit assessments. The findings indicate that ESG disclosure improves internal financial performance but exerts only a limited influence on external financial perceptions within Indonesia’s corporate landscape.